How to Select and Prioritize Water Main Replacement. Issue 10 (1st October 2015) - Garcia, Darlene; Funchion, Susan
Abstract : Colorado Springs Utilities' staff learned how critical it is to understand the entire water system's health so the staff could prioritize main replacement and perform advanced condition assessment.